Bantuan Kemanusiaan Korban Banjir Bandang di Sulawesi Tengah: Humanitarian Assistance for Flash Flood Victims in Central Sulawesi - Fahmi Hafid; Nasrul Nasrul; Aminudin Aminudin; Amsal Amsal; Masudin Masudin; Gusman Gusman; Sova Evie; Kadar Ramadhan; Hamsiah Hamsiah; Junaidi Junaidi; Zainul Zainul; Lisnawati Lisnawati; Putu Candriasih; Nurjaya Nurjaya; Elvyrah Faisal; Linda Linda; Moammar Safari; Supriadi Abd Malik; Andi Fatmawati; Hasnawati Hasnawati; Selvi Alfrida Mangundap; Mardani Mangun; Fajrillah Kolomboy; Dedi Mahyudin Syam; Hastuti Usman; Nurarifah Nurarifah; Tjitrowati Djaafar; Niluh Nita Silfia; Lili Suryani; Sri Restu Tempali; Sigit M. Nuzul; Lisda Widianti Longgupa; Hadina Hadina; Sri M. Hasan; Hadriani; I Wayan Supetran; Mercy Joice Kaparang; Lindanur Sipatu; Baharuddin Condeng; Azizah Saleh; Siti Hadijah Batjo; Djadid Subchan; Anna Veronika Pont; Olkamien J. Longulo; Novarianti Novarianti; Supriadi; Wijianto Wijianto; Sri Yanti Kusika; Henrietta Imelda Tondong; Christina Entoh; Nurfatimah Nurfatimah; Masda Masda; Saman Saman; Yasmin H Yasmin H; Azwar Azwar; Hasni Hasni; Ekasari Dewi Pertiwi; Rusneni; Raoda; Hasdrini; Salman; Irsanty Collein; Yulianus Sudarman H Melangka; Christine; Taqwin Taqwin; Hanum Sasmita; Asri Widyayanti; Ros Arianty; Dwi Kartika; Baiq Emy; Diah Ayu Hartini; Sukmawati; Nitro Galenso; Wery Aslinda; Indro Subagyo; Elfyrah Faisal; Ansar Ansar; Bahja Bahja; Dwi Erma Kusumawati; Agusrianto Agusrianto; Nirva Rantesigi; Rina Tampake; Sony Bernike Magdalena Sitorus; Helena Pangaribuan; Firdaus Hi Jahja Kunoli; Hasbunsyah Hasbunsyah; Metrys Ndama; Nurindah Nurindah; Diana Nurhayati Sinurat; Asrawaty Asrawaty; Abd Farid Lewa; Muliani Muliani; Eka S. Riyanto; Dafrosia Darmi Manggasa; Ni Made Ridla Nilasanti Purwata (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2022)
The flash flood disaster hit Galumpang Village, Aung Village and Bajungan Village in Tolitoli Regency, Central Sulawesi on Wednesday morning 23 March 2022. Due to the large number of victims of flash floods and the urgent needs of victims of flash floods, the Civitas Academic of Poltekkes Kemenkes Palu provided humanitarian aid for victims of flash floods in Tolitoli Regency, Central Sulawesi. Humanitarian assistance in the form of ready-to-eat food, rice, Toothpaste, Soap, Sunlight, Shampoo, Sweetened Condensed Milk, Tea, Sugar, Bucket, Dipper, Mask and Pampers Children under two. The assistance was handed over by the Chief Community Service Officer to the Head of Galumpang Village on April 1, 2022 at the Disaster Management Command Post in Galumpang Village, Dakopamean District, Tolitoli Regency, Central Sulawesi. The flash flood victim’s community as beneficiaries have received assistance from the Poltekkes Kemenkes Palu Academic Community through Community Service activities. ABSTRAK Bencana banjir bandang telah menghantam Desa Galumpang, Desa Aung dan Desa Bajungan di Kabupaten Tolitoli, Sulawesi Tengah pada Rabu dini hari tanggal 23 Maret 2022. Oleh karena besarnya jumlah korban banjir bandang dan kebutuhan korban banjir bandang yang mendesak, maka Civitas Akademika Poltekkes Kemenkes Palu memberikan bantuan kemanusiaan korban banjir bandang di Kabupaten Tolitoli Sulawesi Tengah. Bantuan kemanusian berupa makanan siap saji, beras, Pasta Gigi, Sabun, Sunlight, Shampoo, Susu Kental Manis, Teh, Gula Pasir, Ember, Gayung, masker dan Pampers Baduta. Bantuan diserahkan oleh Ketua Pelaksana Pengabdian Masyarakat kepada Kepala Desa Galumpang pada tanggal 01 April 2022 di Posko Induk Penanggulangan Bencana Desa Galumpang Kecamatan Dakopamean Kabupaten Tolitoli, Sulawesi Tengah. Masyarakat korban banjir bandang sebagai penerima manfaat telah menerima bantuan dari Civitas Akademika Poltekkes Kemenkes Palu melalui kegiatan Pengabdian Masyarakat.